COVID-19 Isolation Control Proposal via UAV and UGV for Crowded Indoor Environments: Assistive Robots in the Shopping Malls - Muhammet Fatih Aslan; Khairunnisa Hasikin; Abdullah Yusefi; Akif Durdu; Kadir Sabanci; Muhammad Mokhzaini Azizan (FRONTIERS, 2024)
Indexed by WOS/ERA